PENINGKATAN KEMAMPUAN PROBLEM SOLVING SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI IMPLEMENTASI PENDEKATAN PEMBELAJARAN KREATIF DI KELAS VII A SMP NEGERI 1 KETUNGAU HULU - YULIANA, YULIANA (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2023)
The purpose of this research is to determine the implementation of a creative learning approach to improve the problem solving abilities of class VII A students at SMP Negeri 1 Ketungau Hulu and to determine the increase in problem solving abilities of class VII A students at SMP Negeri 1 Ketungau Hulu after using the creative learning approach. The type of research used is the Kemmis and Mc Taggart model of classroom action research which consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were 29 students in class VII A of SMP Negeri 1 Ketungau Hulu. The data collection techniques used are observation, documentation and tests. The results of this research show that there is an increase in the problem solving abilities of class VII A students at SMP Negeri 1 Ketungau Hulu in mathematics subjects. After using a creative learning approach, the problem solving abilities of class VII A students at SMP Negeri 1 Ketungau Hulu increased. In the pre-cycle, the average score for students' problem solving abilities was 60.98, classical completeness was 37.93%, and was included in the sufficient criteria. In cycle I, the average score for students' problem solving abilities was 73.91, classical completeness was 65.51%, and was included in the sufficient criteria. In cycle II the average score for students' problem solving abilities was 83.79, classical completeness was 93.10%, and was included in the good criteria. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pelaksanaan pendekatan pembelajaran kreatif untuk meningkatkan kemampuan problem solving siswa kelas VII A SMP Negeri 1 Ketungau Hulu dan untuk mengetahui peningkatan kemampuan problem solving siswa kelas VII A SMP Negeri 1 Ketungau Hulu setelah digunakan pendekatan pembelajaran kreatif. Jenis penelitian yang digunakan adalah penelitian tindakan kelas model Kemmis dan Mc Taggart yang terdiri dari empat tahap, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas VII A SMP Negeri 1 Ketungau Hulu yang berjumlah 29 orang siswa. Teknik pengumpulan data yang digunakan adalah observasi, dokumentasi, dan tes. Hasil penelitian ini menunjukkan bahwa ada peningkatan kemampuan problem solving siswa kelas VII A SMP Negeri 1 Ketungau Hulu pada mata pelajaran matematika. Setelah digunakan pendekatan pembelajaran kreatif, kemampuan problem solving siswa kelas VII A SMP Negeri 1 Ketungau Hulu mengalami peningkatan. Pada pra siklus nilai rata-rata kemampuan problem solving siswa adalah 60,98, ketuntasan klasikal 37,93%, dan masuk dalam kriteria cukup. Pada siklus I nilai rata-rata kemampuan problem solving siswa adalah 73,91, ketuntasan klasikal 65,51%, dan masuk dalam kriteria cukup. Pada siklus II nilai rata-rata kemampuan problem solving siswa adalah 83,79, ketuntasan klasikal 93,10%, dan masuk dalam kriteria baik.